Perbandingan Dewan Perwakilan Daerah (DPD RI) dengan Negara Lain - Abustan Abustan (Universitas Batanghari Jambi, 2020)
The basic idea of the establishment of DPD is the desire to better accommodate regional aspirations and also give a major role to the region in the political decision-making process for matters relating to the region. In the document of Strategic Plan (Renstra) of the House of Regional representatives (DPD) period 2015-2019 mention that the main objective of DPD RI is the realization of DPD RI as one of the State institutions that play an active role and maintain a balance in the state authority in the field of legislative, through the optimization of the implementation of the parliamentary function. The problem formulation in this journal is how to increase the status of DPD in establishing and strengthening the political representation in Indonesia and how to setup the authority of the Regional Representative Council (DPD) Republik Indonesia (RI) when compared with other countries. The discussion in this journal is the change of UUD 1945 to change the system of representatives in the state of Indonesia that previously did not reveal the actual representation. With the presence of the DPD, in the Indonesian representative system, the DPR is supported and should be strengthened by the DPD. With such conditions, the DPD institution has a very high legitimacy, which should have a high formal authority anyway, but in reality the formal authority is very low. The arrangement of the authority of DPD must be done through the Fifth Amendment UUD 1945. This is necessary for the DPD to have a constitutional certainty, so it will guarantee the continuity of the performance of DPD in the present and future. This arrangement is done by considering two things: first, Dpdas the same representative institution with the House of Representatives, should be engaged optimally in the process of making political decisions nationally. Secondly, the Fifth Amendment of the UUD 1945 is intended to assert the DPD as an institution that holds the authority to form legislation; Has a function of legislation; budget function; and surveillance functions; Then to change the articles that have been debilitating the DPD, namely related to the authority to file a RUU, discussing the RUU and also give the last consideration, this change is also done so that the DPD can then supervise with the giving of the right to ask questions, the right to ask for information and the right of a questionnaire and DPD RI through its tools (honorary body) in charge of implementing the code, is expected to always evaluate and revise the rules of DPD RI that is deemed to be no So ideally, do a comparison of the code of ethics with other countries, in order to minimize the misuse of budgets, duties and authorities.